Pilgrimage activities in the territory of the Taurida Diocese before the establishment of the Taurida Department of the Imperial Orthodox Palestinian Society: based on materials from regional church periodicals (1869-1899) - Astapov, Aleksei Anatol'evich (Genesis: исторические исследования, 2025)
The subject of this study is the internal and external pilgrimage activity in the territory of the Taurida diocese during the period leading up to the opening of the Taurida department of the Imperial Orthodox Palestine Society, which took place on April 2/15, 1900. The main source used is materials from regional church-related periodicals – the Tauride diocesan statements from 1869 to 1899. The author pays special attention to identifying and localizing the main pilgrimage sites in the Crimea peninsula and the adjacent Northern Taurida, recreating logistical schemes for external pilgrimages from the Taurida province beyond the borders of the Russian Empire, and determining the regional features of pilgrimage to the saints of Palestine and Mount Athos in the second half of the 19th century, including clergy and monastics of the Taurida diocese. The primary method of the research is a systematic approach that reveals the features of pilgrimage activity at both the particular (local) level and the macro level, wherein the territory of the Taurida province becomes a unique transshipment base on the way to the centers of world Christian pilgrimage. The comparison of the two levels necessitates the use of a comparative method, which allows for assessments of their autonomy and interrelation. The novelty of the research lies in the fact that the author provides the first historical overview of the main centers of internal pilgrimage that were established based on male and female monasteries of the Crimea peninsula and Northern Taurida. It has been found that most monasteries faced difficulties in accommodating pilgrims, particularly during the eve and days of patronal feasts. The life of pilgrims who were unable to find lodging in hotels is described. The article reports on the interaction between the Palestine Commission, and later the Imperial Orthodox Palestine Society, with the episcopate of the Taurida diocese. The names of clergy and nuns from the Taurida diocese who visited Palestine and Athos in the 19th century are mentioned. The main routes of external pilgrimage – via Sevastopol and Odessa – are discussed. The main conclusion of the study is that the internal and external pilgrimage activities in the Taurida diocese are independent phenomena, as neither the local diocesan leadership nor the clergy and monastics in the second half of the 19th century, apart from conducting the annual Palm Sunday gathering, participated in organizing or accompanying pilgrimages to the Holy Land and Athos.